STUDI KERAPATAN DAN POLA PEMENCARAN LAMUN DI PESISIR PULAU UNGGEH KABUPATEN TAPANULI TENGAH PROVINSI SUMATERA UTARA - Romanda Mora Tanjung; Pindi Patana; Amanatul Fadhilah (AQUACOASTMARINE, 2017)
This research aimed to know the density and pattern of dissemination of seagrass in Unggeh island. This research was conducted in Unggeh Island, Badiri Sub-district, Central Tapanuli Regency, North Sumatera Province in April 2017. The research method used is Purposive Sampling and divided into 3 stations. The result of seaweed density for Enhalus acoroides species of the station I is 35 ind/m2, station II is 42 ind/m2, and station III is 10 ind m2, with the average of 29 ind/m2. The species of Cymodocea serrulata of station I is 364 ind/m2, station II is 331 ind/m2, and station III is 219 ind/m2 with the average of 305 ind/m2. Halodule pinifolia species only is found in station III with a density of 36 ind/m2 with the average of 12 ind/m2. Based on the calculation of dispersal pattern for Enhalus acoroides, the result is 0,56 which means to be uniform, Cymodocea serrulata 0,50 which means to be uniform and Halodule pinifolia 1,05 which means to be in groups.Keywords ; Seagrass, Density, Pattern of Dissemination, Unggeh Island.